The Performance of Aviation Security Personnel Services at Sentani Airport - Muhammad Fauzi; Aswanti Setyawati; Jermanto Setia Kurniawan (Institut Transportasi dan Logistik Trisakti, 2021)
Some of the efforts that can be made to improve aviation security performance are by implementing security screening and airport security programme. The study was conducted at Sentani Airport in 2019 using quantitative methods, with the number of research samples taken in total saturation of 50 personnel at Sentani Airport. Data collected through instruments in the form of statement sheets with ordinal scale models that have been tested, linear regression, partial or simultaneous. The research is using path analysis technique. Based on the results of the study show that security screening has a direct effect on flight aviation security of 2.224 and there is a direct influence of airport security programme on Aviation Security Performance of 4.186 and there is a significant positive effect of security screening on airport security programme is 5.491 and based on the results of the study shows that Security screening indirectly has an effect of 1320,879 on Aviation Security Performance through mediation of Airport Security Programme.